2020
DOI: 10.1101/2020.05.29.20116731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence Among All Workers in a Teaching Hospital in Spain: Unmasking The Risk

Abstract: Background: Health-care workers (HCW) are at increased risk for SARS-CoV-2 infection, but few studies have evaluated prevalence of antibodies against SARS-CoV-2 among them. Objective: To determine the seroprevalence against SARS-CoV-2 in all HCW. Methods. Cross-sectional study (April 14th- 27th , 2020) of all HCW at Hospital Universitario Fundacion Alcorcon, a second level teaching hospital in Madrid, Spain. SARS-CoV-2 IgG was measured by ELISA. HCW were classified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 41 publications
3
34
2
Order By: Relevance
“…A voluntary asymptomatic screening programme offering SARS-CoV-2 PCR and antibody testing to all staff working anywhere on site commenced on 23 rd April 2020. Between 23 rd April and 8th June, 10,610 of the 13,800 (77%) staff employed by OUH registered for asymptomatic testing and 10,034 (73%) were tested at least once, 9926 by PCR and 9958 by serology. The majority of testing was undertaken in the first three weeks of May 2020 ( Figure 1C).…”
Section: Asymptomatic Staff Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A voluntary asymptomatic screening programme offering SARS-CoV-2 PCR and antibody testing to all staff working anywhere on site commenced on 23 rd April 2020. Between 23 rd April and 8th June, 10,610 of the 13,800 (77%) staff employed by OUH registered for asymptomatic testing and 10,034 (73%) were tested at least once, 9926 by PCR and 9958 by serology. The majority of testing was undertaken in the first three weeks of May 2020 ( Figure 1C).…”
Section: Asymptomatic Staff Testingmentioning
confidence: 99%
“…However, crucial to designing a safe working environment and maintaining effective healthcare services is an understanding of the risks associated with specific roles and to individuals, and whether risk is associated with social-mixing, direct exposure to Covid-19 patients or PPE type. Some studies have suggested exposure to Covid-19 patients poses increased risk ( Nguyen et al, 2020 ; Ran et al, 2020 ; Lombardi et al, 2020 ), whilst others have not ( Hunter et al, 2020 ; Galan et al, 2020 ; Folgueira et al, 2020 ). However, none have addressed these questions by comprehensively investigating all staff groups across an institution, simultaneously assessing symptomatic and asymptomatic incidence.…”
Section: Introductionmentioning
confidence: 99%
“…As reported during the SARS-CoV-1 epidemic, HCWs working in SARS medical wards had higher seroprevalence than those working in general medical wards [18]. Moreover, it is only common-sensical to assume that HCWs working in COVID-19 receiving facilities will be at a higher risk to contract COVID- 19. Surprisingly, the frequency of positive SARS-CoV-2 antibodies for the non-COVID-19 receiving hospital was 32.7% as compared to 28.2% in COVID-19 receiving hospital (p=0.129).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported during the second phase of the epidemic in China that among the 42,600 HCWs who were deployed in Hubei province to serve the COVID-19 cases, none were infected with SARS-CoV-2 [9]. In contrast, it has been reported from Spain that seroprevalence of SARS-CoV-2 was less frequent (25.8%) in low-risk areas as compared to medium-(33.8%) and high-risk areas (33.1%) (p=0.007) [19]. The findings of the Spanish study could be attributed to the fact that it was conducted only in COVID-19 receiving hospitals with no comparison made with a non-COVID-19 receiving hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation